2009
DOI: 10.1901/jaba.2009.42-343
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Interaction Between Quality of Attention and Negative Reinforcement With Children Who Display Escape‐maintained Problem Behavior

Abstract: The choice-making behavior of 2 typically developing children who engaged in problem behavior maintained by negative reinforcement was evaluated within a concurrent-operants assessment that varied the quality of attention across free-play and demand conditions. The results demonstrated that it was possible to bias responding towards academic demands for both participants by providing high-quality attention, despite the continuous availability of negative reinforcement. The current study extended brief clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 11 publications
5
35
1
4
Order By: Relevance
“…Com o decorrer do tempo, pode-se dizer que os familiares caíram em uma "armadilha de reforçamento negativo", isto é, cediam ao que a criança queria (reforço positivo) como forma de se livrar (reforço negativo) da situação aversiva de "teimosia", como mostra o estudo realizado por Gardner (2006), reforçando, assim, o comportamento que desejavam suprimir e levando ao desenvolvimento de um padrão coercitivo de interação infantil (Sidman, 1995).…”
Section: Análise Funcional Do Casounclassified
See 3 more Smart Citations
“…Com o decorrer do tempo, pode-se dizer que os familiares caíram em uma "armadilha de reforçamento negativo", isto é, cediam ao que a criança queria (reforço positivo) como forma de se livrar (reforço negativo) da situação aversiva de "teimosia", como mostra o estudo realizado por Gardner (2006), reforçando, assim, o comportamento que desejavam suprimir e levando ao desenvolvimento de um padrão coercitivo de interação infantil (Sidman, 1995).…”
Section: Análise Funcional Do Casounclassified
“…Consequentemente, livrava-se da atividade que não queria ou não sabia fazer, conseguindo que a terapeuta mudasse de atividade e acatasse sua sugestão. A terapeuta percebeu que, assim como a família, sua atitude, embora contornasse a situação desagradável em sessão, também reforçava positivamente (deixar que ele fizesse o que queria) e negativamente (não realizar a proposta da terapeuta) o comportamento opositor e agressivo da criança, esquivando-se da situação (Gardner, 2006;Sidman, 1995).…”
Section: Análise Funcional Da Intervenção Iunclassified
See 2 more Smart Citations
“…Although type of language has not been investigated as an independent variable during FCT, previous studies have shown that variables related to language may impact the results. For example, the type of language used in FCT might be based on variables such as how language increases the effort in emitting the mand (Horner and Day 1991; Richman et al 2001), the child’s preference for specific types of mands (Harding et al 2009; Winborn et al 2002; Winborn-Kemmerer et al 2009), or the quality of attention provided by the parent (Gardner et al 2009; Peck et al 1996). …”
mentioning
confidence: 99%